INTERRELATION BETWEEN MITOCHONDRIAL ENZYME ACTIVITY AND ANTIOXIDANT ACTIVITY OF SECONDARY POLYPHENOL NATURE METABOLITES IN HEMIPARASITE VISCUM ALBUM L. LEAVES - S. L. Adzhiakhmetova; D. I. Pozdnyakov; N. M. Chervonnaya; E. O. Kulichenko; E. T. Oganesyan (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2022)
Antioxidants are widely used in practical medicine. Not only the search for new plant antioxidants, but also the study of the factors affecting their accumulation in plants, are relevant.The aim is to study the interrelation between the activity of mitochondrial enzymes and the antioxidant activity of the secondary polyphenolic nature metabolites in hemiparasite Viscum Album L. leaves.Materials and methods. The sampling material was Viscum album L. leaves, collected in winter from a host tree, Malus domestica Borkh. The extraction of biologically active substances was carried out with ethyl alcohol of various concentrations (90%, 70% and 50%), or purified water. The amount of total antioxidants was estimated by the amperometric method. The amount of total phenols was evaluated in the reaction with the Folin-Ciocalteu reagent. The concentration of total flavonoids was estimated by the change in the optical density of the rutin with aluminum (III) chloride complex. The antioxidant properties of the analyzed extracts were determined in vitro in the induced lipid peroxidation test. The activity of aconitase was assessed by a conjugated aconitase-isocitrate dehydrogenase reaction, citrate synthase - by changing the color intensity of the Ellman reagent solution, succinate dehydrogenase were determined in the reaction of succinate-dependent oxidation of 2,6-dichlorophenolindophenol.Results. The carried out study showed that the maximum amount of total phenols (2.39±0.05%) is observed in a 50% ethanol extract from Viscum album L. leaves, with the content of total flavonoids equal to 1.83±0.04%, and the antioxidants equal to 0.503±0.007 mg/g (a quercetin equivalent) and 0.322±0.006 mg/g (a gallic acid equivalent). A 50% ethanol extract suppressed lipid peroxidation in the model mixture with IC50=106.3±1.09 µg/ml. In Viscum album L. leaves, a high activity of aconitase which strongly correlated (r=0.88416) with changes in the concentration of flavonoids, has been notified.Conclusion. The optimal extractant for obtaining extracts with a high antioxidant activity is 50% ethyl alcohol. The analysis of the mitochondrial enzymes activity showed that in Viscum album L. leaves collected in winter, a high activity of aconitase strongly correlated with changes in the concentration of flavonoids (r=0.88416).